KATALISASI INFORMASI PUBLIK TERHADAP PENGGUNAAN DANA DESA SEBAGAI BENTUK AKUNTABILITAS KEUANGAN DI DESA BUHU JAYA - Tome, Abdul Hamid; Kadir, Muhamad Khairun Kurniawan (MAJU : Indonesian Journal of Community Empowerment, 2024)
Publication efforts are possible using information systems, especially those that are digital-based. The existence of a new model in the realm of village fund management publications will realize accountable and transparent village fund management. Therefore, this service is carried out in the form of counseling on planning and using village funds based on accountability values, Microsoft-based village financial management training and the formation of village information media. The final result of the implementation of the service which forms a digital-based village information social media is one form of realizing transparency and accountability in the use of village funds. The existence of this series of activities is a step in realizing accountable and transparent management of village funds so that it will avoid misuse of village funds as well as provide space for community participation in supervising the management of village funds. In addition, this media will provide space for community participation in monitoring the use of village funds carried out in various forms of programs and activities.